2013
DOI: 10.1021/jp403856e
|View full text |Cite
|
Sign up to set email alerts
|

Some Unexpected Behavior of the Adsorption of Alkali Metal Ions onto the Graphene Surface under the Effect of External Electric Field

Abstract: In this work the interaction between alkali metal ions and graphene surface with the absence and the presence of external electric field applied perpendicular to the surface was investigated. M05-2X/6-31G(d) DFT calculations were performed to describe the adsorption properties. Results show that the electric field pushes closer the positively charged ion to the graphene, where the charge transfer between the alkali metal cations and the electron rich graphene surface increases. At a species-dependent certain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 28 publications
2
24
2
Order By: Relevance
“…Optimized structures of benzene interacting with halide ions indicate that the π‐electron clouds of benzene show strong repulsion with incoming halide ions and cause them to be associated mainly with the terminal H atoms instead of being situated on top of the benzene ring as in the case of graphene (Figure ) . This also validates the present graphene models, which have been widely used before …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Optimized structures of benzene interacting with halide ions indicate that the π‐electron clouds of benzene show strong repulsion with incoming halide ions and cause them to be associated mainly with the terminal H atoms instead of being situated on top of the benzene ring as in the case of graphene (Figure ) . This also validates the present graphene models, which have been widely used before …”
Section: Resultssupporting
confidence: 82%
“…In line with previous studies, a graphene monolayer with 19 aromatic rings (Figure a) was used for adsorption of halide ions (X − ) and metal ions (M + ). The graphene structure has the chemical formula of C 54 H 18 when passivated with H atoms.…”
Section: Computational Detailsmentioning
confidence: 86%
“…Aside from the substituents on a π-framework, it has been shown that an external electric field (EEF) can modulate the bonding properties of the ion-π systems. 26,27,28,29 In the following after a brief introduction to the effect of an EEF on electronic energy of our model systems in Section 1.2, and describing the computational methods (Section 2) we study the effect of substituents and an EEF on the bonding between a number of singly charged ions and substituted coronenes. Variations of the binding energy, electronic properties, and electric response properties of the substituted coronenes are investigated in the absence and presence of an EEF in Section 3.…”
Section: Ion-π Interactionmentioning
confidence: 99%
“…Colherinhas et al [56] conduct DFT calculations and indicate that the adsorption strength of metal ions on grapheme is closely associated with the radius and charge of metal ions. The adsorption configurations with the highest stability correspond to the hollow site (H-site) where metal ions are situated at the center of an aromatic ring, as a result of maximizing the cation-π interactions [57]. As indicated by Addition of water molecules may significantly weaken the binding between metal ions on grapheme [58].…”
Section: +mentioning
confidence: 99%